Association of Long‐Term Exposure to PM2.5 Constituents and Green Space With Arthritis and Rheumatoid Arthritis - Yi‐Sheng He; Yi‐Qing Xu; Fan Cao; Zhao‐Xing Gao; Man Ge; Tian He; Peng Zhang; Chan‐Na Zhao; Peng Wang; Zhiwei Xu; Hai‐Feng Pan (GeoHealth)
Abstract There is limited evidence regarding the effects of long‐term exposure to PM2.5 constituents on the risk of arthritis and rheumatoid arthritis, and the interaction between PM2.5 and green space remains unclear. This study examined the relationship between long‐term exposure to PM2.5 constituents and the risk of arthritis and rheumatoid arthritis, with the exposure period extending from recruitment until self‐reported outcomes, death, loss to follow‐up, or end of follow‐up. Additionally, the study assessed whether there was an interactive effect between PM2.5 and green space on these risks. We gathered cohort data on 18,649 individuals aged ≥45 years. We applied generalized linear mixed‐effects models to estimate the effects of PM2.5 constituents, NDVI, and their interaction on arthritis and rheumatoid arthritis. The quantile g‐computation and weighted quantile sum regression model were applied to estimate the combined effect of PM2.5 constituents. Our results showed that exposure to single and mixed PM2.5 constituents adversely affected arthritis and rheumatoid arthritis, and was mainly attributed to the black carbon component. We observed “U” or “J” shaped exposure‐response curves for the effects of PM2.5, OM, NO3− and NH4+ exposure on the development of arthritis/rheumatoid arthritis. Additionally, the odds ratio of arthritis for per interquartile range (IQR) increase in PM2.5 was 1.209 (95% CI:1.198, 1.221), per 0.1‐unit decrease in NDVI was 1.091 (95% CI:1.033, 1.151), and the interaction term was 1.005 (95% CI:1.002, 1.007). These findings flesh out the existing evidence for PM2.5 constituents, NDVI and arthritis, rheumatoid arthritis, but the underlying mechanisms still require further exploration.